Institutional Transformation and Development in the Engineering Education to meet the Volatility, Uncertainty, Complexity and Ambiguity (VUCA) - Vedhathiri, Thanikachalam (Journal of Engineering Education Transformations, 2018)
Engineering education is facing volatility, uncertainty, complexity, and ambiguity in the last seventeen years due to fast developing global industries which established manufacturing units in India under foreign direct investment (FDI). The needs of these global industries are based on the high-quality products which were exported to the European countries and to the rest of the world. Some of the engineering institutions could modernize the curriculum, improve the resources, infrastructure, faculty's skills and competencies but the explosive growth of the institutions in the private sector could not meet the challenges. They need strategic planning, training their faculty members, improve their infrastructure and modernize the resources. They must focus on globalization and offer high-end programs. The faculty needs accelerated leadership programs. They need global thinking and mindset.